Mechanical, thermal, and morphological properties of graphene reinforced polycarbonate/acrylonitrile butadiene styrene nanocomposites - Pour, R. H. (John Wiley and Sons Inc., 2016)
Nanocomposites of polycarbonate/acrylonitrile butadiene styrene (PC/ABS) with (70/30) composition containing different amounts of graphene nanoplates (GNPs) (1, 3, and 5 wt%) were prepared by melt-blending in a twin-screw extruder. The structural, morphological, mechanical, and thermal properties of the nanocomposites were investigated. The Young's modulus and flexural modulus of the nanocomposites were increased by 30 and 54%, respectively, when 3 wt% GNPs was added. The flexural strength and tensile strength of the PC/ABS/GNPs nanocomposites increased up to a loading of 3 wt% GNPs. The incorporation of GNPs enhanced the thermal stability and char yield of the nanocomposites. X-ray diffraction and field emission scanning electron microscopy showed uniform dispersion and alignment of GNPs in PC/ABS matrix. The interaction between the GNPs and the PC/ABS matrix were confirmed by Fourier transform infrared spectra. Therefore, the PC/ABS/GNP nanocomposites with improved flexural and tensile properties, without loss of extensibility and good thermal properties may have promising applications in automotive, electric tools, household, communication, and safety appliances.